THE CONCEPT OF HAND-CATCHING OPERATIONS (OTT) BY THE CORRUPTION ERADICATION COMMISSION (KPK) INPERSPECTIVE LEGAL CERTAINTY - Rabiyatul Adawiyah; Muhammad Erham Amin; Anang Shophan Tornado (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study is to analyze the Hand-Catching Operation (OTT) system carried out by the Corruption Eradication Commission and also how the Effectiveness of the Hand-Catching Operation Position (OTT) carried out by the Corruption Eradication Commission (KPK) in the perspective of legal certainty. The type of research used is normative legal research by collecting andanalyze legal material related to the issue to be discussed. As well as comparing several judge's decisions related to the one in question. The results of this study are that the Hand-Catching Operation is an Illegal Action or an arrest where this action can be a reason for carrying out a Pretrial, in which the meaning of Hand-Catching Operation (OTT) still does not have a clear meaning, legal basis and direction. Because the Hand-Catching Operation (OTT) does not have clear regulatory basis in Corruption Crimes, it follows from the juridical implications of the process of investigating Corruption criminal cases. The Hand-Catching Operation carried out by the Corruption Eradication Commission is also an act of Super Power because it is not contained in the Criminal Procedure Code (KUHAP), so the concept of Hand-Catching Operation is still a question mark against the legal framework